KEBEBASAN BERKONTRAK DAN PERLINDUNGAN KONSUMEN DALAM PERJANJIAN SEWA MENYEWA PADA SEBUAH KESEIMBANGAN HUKUM - Mifta Nur Feriska (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research discusses the balance between freedom of contract and consumer protection in the context of rental agreements. The main focus is on how the law creates a balanced framework to ensure justice and equal rights for the parties involved. First of all, the basic meaning of a rental agreement is presented based on Article 1548 of the Civil Code, with four mandatory elements that must be fulfilled. Freedom of contract, as a basic principle, gives the parties involved the ability to determine and carry out agreements according to their wishes, but remains limited by legal, ethical and moral norms. The role of Consumer Protection Laws is explained as an effort to prevent abuse of power by contractual parties and protect consumers from harmful practices. Socialization of this law is important to increase consumer awareness and knowledge, especially among those with low levels of education. This research also reviews the balance between the rights and obligations of business actors and the rights and obligations of consumers, highlighting more specific regulations in the Consumer Protection Law. This balance creates a fair and ethical business environment. Next, the principles of balancing between freedom of contract and consumer protection in rental agreements are explained. This includes clarity of contracts, protection against unfair practices, freedom of contract with limitations, protection against discrimination, and lawsuit and dispute resolution rights. Restrictions on freedom of contract are described as steps taken by law to protect consumers from exploitation or harmful practices in rental agreements. By detailing fair rental prices, late payment provisions, privacy rights, repair rights, and the right to withdraw from the contract, the law aims to create equality between the parties involved. Ultimately, the study concludes that the balance between freedom of contract and consumer protection in rental agreements requires careful attention. These principles must be regulated in such a way as to safeguard consumer rights without hampering the development of legitimate business activities. With a good understanding of applicable regulations, this balance can be achieved to create a healthy and fair business environment.